2008
DOI: 10.1021/jp711166d
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement and Hydrogen Scrambling Pathways of the Toluene Radical Cation: A Computational Study

Abstract: A computational study is undertaken to provide a unified picture for various rearrangement reactions and hydrogen scrambling pathways of the toluene radical cation (1). The geometries are optimized with the BHandHLYP density functional, and the energies are computed with the ab initio CCSD(T) method, in conjunction with the 6-311+G(d,p) basis set. In particular, four channels have been located, which may account for hydrogen scrambling, as they are found to have overall barriers lower than the observed thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The bond angles also exhibit a proportionate deviation to facilitate the 1,4‐migration 23. Such large geometric distortions in hydrogen migrations have also been reported with different substrates 24…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The bond angles also exhibit a proportionate deviation to facilitate the 1,4‐migration 23. Such large geometric distortions in hydrogen migrations have also been reported with different substrates 24…”
Section: Resultssupporting
confidence: 64%
“…[23] Such large geometric distortions in hydrogen migrations have also been reported with different substrates. [24] The comparison between the proton transfer and hydride transfer involved in L a to M a and M a to Y conversions, respectively, reveals that the proton migratory pathways generally prefer a series of 1,2-migrations, whereas several 1,2migrations in the case of hydride transfer involve relatively higher energy transition states. In the case of zwitterionic intermediate M a only the first 1,2-hydride transfer is found to be favorable.…”
Section: Resultsmentioning
confidence: 99%
“…The [1,3]‐ and [1,4]‐methyl shifts require very high activation energies. Thus, it is logical to conclude that the O ‐ and N ‐alkyl pterins, for example, 3 and 4 , are non‐interconverting species, unlike walk processes observed for molecular rearrangements , such as the walk rearrangement of bicyclo[2.1.0]pent‐2‐ene .…”
Section: Resultsmentioning
confidence: 99%
“…The [1,3]-and [1,4]-methyl shifts require very high activation energies. Thus, it is logical to conclude that the O-and N-alkyl pterins, for example, 3 and 4, are non-interconverting species, unlike walk processes observed for molecular rearrangements (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), such as the walk rearrangement of bicyclo[2.1.0]pent-2ene (44). Table 5 lists the computed log P and log D values that were obtained with the ChemAxon algorithm.…”
Section: Dft Computed Stabilities Of Alkyl Pterin Regioisomersmentioning
confidence: 99%
“…The one directly connecting 1 + and 3 + , originally proposed by Dewar and Landman, 8 consists of a [1,3]-H shift, whereby the methyl hydrogen migrates to the ortho-position to form 3 + , followed by an intramolecular cyclization to form the transient distonic radical cation 6 + , which readily undergoes ring expansion to produce 5 + . However, quantum chemical calculations 22 have shown that it is more favorable to first form 2 + and then 3 + than to directly convert 1 + to 3 + . According to ab initio calculations the Hoffman mechanism is energetically slightly preferred over the Dewar−Landman mechanism.…”
Section: Introductionmentioning
confidence: 99%